1995
DOI: 10.1111/j.1752-7325.1995.tb02356.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of College Football Coaches Regarding NCAA Mouthguard Regulations and Player Compliance

Abstract: Coaches view themselves, the players, or the trainer as most responsible for players wearing mouthguards, not referees. This finding coincides with the officials' opinion that the coaches should be accountable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…Several previously published studies have investigated barriers to mouthguard use, identifying a multitude of potential issues including construction (e.g., durability, cost, fit, comfort, and availability; DeYoung, Robinson, & Godwin, 1994; Gardiner & Ranalli, 2000), players’ perceptions of mouthguards (e.g., factors such as a lack of knowledge of injury risk or mouthguard effectiveness and concerns over decreased comfort, ability to communicate, and athletic performance; Berry, Miller, & Leow, 2005; DeYoung et al, 1994; Gardiner & Ranalli, 2000; Hawn, Visser, & Sexton, 2002; Maestrello-deMoya & Primosch, 1989; Morton & Burton, 1979), peer pressure, and the attitudes, knowledge, and beliefs of parents (Diab & Mourino, 1997; Gardiner & Ranalli, 2000; Pribble, Maio,& Freed, 2004; Walker, Jakobsen,& Brown, 2002), coaches (Berg et al, 1998; Gardiner & Ranalli, 2000; Hawn et al, 2002; Ranalli & Lancaster, 1995), and referees/officials (Gardiner & Ranalli, 2000; Hawn et al, 2002; Lancaster & Ranalli, 1993). Similar to previous studies, we found that overall, among both athletes who have a mouthguard but never wear it and athletes who do not have one and have made a decision not to wear one, the main reasons for not doing so were similar; that is, they were not required to wear one (65.3 %) and they felt they could not breathe or talk while wearing one (61.5 %).…”
Section: Discussionmentioning
confidence: 99%
“…Several previously published studies have investigated barriers to mouthguard use, identifying a multitude of potential issues including construction (e.g., durability, cost, fit, comfort, and availability; DeYoung, Robinson, & Godwin, 1994; Gardiner & Ranalli, 2000), players’ perceptions of mouthguards (e.g., factors such as a lack of knowledge of injury risk or mouthguard effectiveness and concerns over decreased comfort, ability to communicate, and athletic performance; Berry, Miller, & Leow, 2005; DeYoung et al, 1994; Gardiner & Ranalli, 2000; Hawn, Visser, & Sexton, 2002; Maestrello-deMoya & Primosch, 1989; Morton & Burton, 1979), peer pressure, and the attitudes, knowledge, and beliefs of parents (Diab & Mourino, 1997; Gardiner & Ranalli, 2000; Pribble, Maio,& Freed, 2004; Walker, Jakobsen,& Brown, 2002), coaches (Berg et al, 1998; Gardiner & Ranalli, 2000; Hawn et al, 2002; Ranalli & Lancaster, 1995), and referees/officials (Gardiner & Ranalli, 2000; Hawn et al, 2002; Lancaster & Ranalli, 1993). Similar to previous studies, we found that overall, among both athletes who have a mouthguard but never wear it and athletes who do not have one and have made a decision not to wear one, the main reasons for not doing so were similar; that is, they were not required to wear one (65.3 %) and they felt they could not breathe or talk while wearing one (61.5 %).…”
Section: Discussionmentioning
confidence: 99%
“…The results are mixed with respect to the take up rate of each type of mouthguard and seem to depend on the sport being played. A study of US college football [65], in which mouthguard wear is compulsory, found that 33% of athletes studied reported using custom‐made mouthguards, 33% both custom‐made and boil‐and‐bite, and 27% only boil‐and‐bite. Chapman’s study of the 1990 Australian rugby union team [11] found that 89% of the squad wore mouthguards professionally fitted by a dentist.…”
Section: Behavioural Aspects Of Mouthguard Wearmentioning
confidence: 99%
“…3,4 The reduction in dental injuries while wearing mouthguards is well documented. [5][6][7] Intraoral dental mouth guards have been classified into 3 categories: stock, self-adapted, and custom-made. 8 Stock mouthguards are inexpensive and come preformed.…”
mentioning
confidence: 99%